Intertekstualitas Film My Annoying Brother: Kajian Perbandingan Versi Korea Selatan dan Indonesia - Karina Salsabila; Fina Diah Ayu Wulandari; Mohamad Afrizal (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
Film as a cultural text never exists independently but is always connected to previous texts that form a network of meanings. The phenomenon of film remakes demonstrates a strong intertextual relationship, as seen in My Annoying Brother in its South Korean and Indonesian versions. This study examines the intertextual relationship between the two films and analyzes the ways the story is reworked within different social and cultural contexts. The purpose of this research is to investigate the intertextual relations between the South Korean version as the source text and the Indonesian version as the transformed text by applying the concepts of opposition, transposition, and transformation. This study employs a qualitative descriptive approach using an observation method through careful and repeated film viewing, accompanied by note-taking of important dialogues and significant scenes. The research data consist of narrative elements of the films, including plot, characters, conflict, setting, and cultural values. The findings reveal that although both films share similar narrative structures and central conflicts, the Indonesian version incorporates local cultural adaptations that generate new meanings within the context of cross-cultural film remakes.